Pengaruh Penyiraman Air Tanah Terhadap Perubahan Sifat Kimia Tanah dan Air Gambut di Kalimantan Tengah - Yulian Taruna; Salampak Salampak; Nina Yulianti; Haiki Mart Yupi; Sustiyah Sustiyah; Fahrul Indrajaya (Fakultas Pertanian Universitas Padjadjaran, 2021)
This study observed the changes in chemical properties of peat soil and ground water after irrigation of two peat types: inland and transition peat. The research was carried out in the Basic and Analytic Laboratory of Palangka Raya University. Inland peat and water samples were obtained from Palangka Raya City, meanwhile and transitional peatland was taken from Pulang Pisau Regency, Central Kalimantan Province. Research methods consisted of survey and experimental test with complete randomized design (CRD) consisted of groundwater irrigation treatment and was repeated 3 times. The experimental parameters are soil chemical properties such as Ash Content, Base Saturation (KB), Nitrogen (N), Phosphor (P), Exchangeable Potassium (K-dd), Interchangeable Sodium (Na-dd), Interchangeable Calcium (Ca-dd), Interchangeable Magnesium (Mg-dd), Cation Exchange Capacity (CEC), Aluminum Saturation, Iron (Fe), Sulfate (SO₄), Hydrogen Concentration (pH), and Electrical Delivery Power (EDP), and water chemical properties such as pH, EDP, cation, and anions.. The results showed that there has been an increase in the value of CEC, P, Na-dd, SO₄, pH, and decreased of Ash Content, N, K-dd, Ca-dd, and EDP on transitional peat soils. Meanwhile, the inland peat soils showed an increase of Ash Content, N, P, Mg-dd, a saturation of Al and Fe, and decreased in the value of CEC, Ka-dd, Na-dd, Ca-dd, SO₄, pH, and EDP. There were similar effect of groundwater irrigation, towards soil chemical properties, with an exeption of iron levels (Fe). Iron levels (Fe) in transitional peat increase, but decreased in inland peat.